2023
DOI: 10.1039/d3ta03683a
|View full text |Cite
|
Sign up to set email alerts
|

Dual-functional reduced graphene oxide decorated nanoporous polytetrafluoroethylene metafabrics for radiative cooling and solar-heating

Abstract: Although passive radiative cooling and active heating are becoming two essential functions for next-generation smart personal thermal management textiles, the integration of opposite cooling and heating into one metafabric with...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(7 citation statements)
references
References 60 publications
0
7
0
Order By: Relevance
“…21 Another strategy is to construct micro- and nano-structures in substrates with high emissivity comprised of pore structures, 22–26 core–shell structures, 27–29 and micro-nano fibrous structures. 30–33 It has been demonstrated that nanofibers with a diameter comparable to the wavelength of the solar spectrum can serve as effective scatters to enable strong solar reflection. 34–37 Thus, fibrous films obtained by the electrospinning process have attracted significant attention in the field of radiation refrigeration due to their advantages of easy regulation of the fiber structure, high air permeability and elevated flexibility.…”
Section: Introductionmentioning
confidence: 99%
“…21 Another strategy is to construct micro- and nano-structures in substrates with high emissivity comprised of pore structures, 22–26 core–shell structures, 27–29 and micro-nano fibrous structures. 30–33 It has been demonstrated that nanofibers with a diameter comparable to the wavelength of the solar spectrum can serve as effective scatters to enable strong solar reflection. 34–37 Thus, fibrous films obtained by the electrospinning process have attracted significant attention in the field of radiation refrigeration due to their advantages of easy regulation of the fiber structure, high air permeability and elevated flexibility.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, due to the high solar thermal conversion efficiency of such materials, the heating side in the dual mode system still maintains a temperature above ambient. 86 Examples of such materials include graphene, 87 carbon nanotubes, and carbon black. According to eqn (4), to achieve the temperature increase, the value of P net needs to be less than 0.…”
Section: Mechanically Responsive Dual Mode Systemmentioning
confidence: 99%
“…Liu et al 19 endowed a smart textile with the function of heat storage and temperature regulation by combining phase-change materials with a 3D conductive network in nonwoven PP. Luo et al 20 integrated opposite cooling and heating functions into metafabric by assembling a nanoporous PTFE radiative cooling substrate with a solar-thermal RGO layer and a PDMS supporting coating. However, the use of optical radiation and photothermal effect might create a serious disadvantage since it can cause skin to burn.…”
Section: Introductionmentioning
confidence: 99%